Effects of host plants on the susceptibility of Cowpea Aphid, Aphis craccivora (Hemiptera: Aphididae) to the entomopathogenic fungus, Beauveria bassiana (Ascomycota, Hypocreales) - Z. Ezzatabadipoor; A. Shirvani; M. Rashki (نامه انجمن حشره‌شناسی ایران, 2015)
In this study, susceptibility of the cowpea aphids, Aphis craccivora Koch (Hemiptera: Aphididae) to entomopathogenic fungus, Beauveria bassiana strain DEBI008 (Ascomycota, Hypocreales) originated from Chorthippus brunneus Tunberg (Orthoptera: Acrididae), fed on the three different bean varieties (pinto bean, kidney bean and cowpea), was investigated under laboratory conditions (at 25 ± 1 °C, 85% RH and a photoperiod of 16L: 8D). One-day-old adult aphids were treated by sublethal concentrations (LC10) of the fungus including 7.4 × 104, 4.3 × 104, and 8 × 104 calculated on pinto bean, kidney bean, and cowpea, respectively. The biological properties of their progeny were analysed using a two-sex fertility life table and TWOSEX-MSChart software. The results showed that the rm, T and ë values of their progeny were significantly different between pinto bean (0.17 ± 0.02, 10.72 ± 0.56 and 1.19 ± 0.02, respectively) and cowpea (0.26 ± 0.01, 9.26 ± 0.25 and 1.30 ± 0.02, respectively). There were no significant differences in the R0 values among the different plant varieties. We found that the fungal treatment significantly decreases fecundity, longevity and life span of the progeny fed on each plant variety. The results indicated that the most favourable effects of B. Bassiana was achieved when the aphids fed on pinto bean, implying the suitability of this variety for integrated management of A. craccivora. But the aphids that were fed on cowpea, suffered less fitness costs from fungul infection ,which reflected the function of host plant in defence of A. craccivora against the pathogen.